Perancangan dan Pembuatan Aplikasi Sistem Administrasi Pada Toko Joyo Motor - Tommy Chandra (Jurnal Infra, 2013)
Joyo Motor Store is a company that sells various kinds of car sparepart. Current manual system made it difficult for the owner to know the company’s profits or losses.Based on the background issues, The author designed of the information system administration for the company. The system consists sales systems, purchasing, inventory records, and displays a report each month making this application using Visual Basic 2005 as a programming language and SQL Server 2005 as its database.Results obtained from applications that have been made, among other one administrative information systems that can create and display various reports. This report is useful to help to see transactions that occur within a certain period. Based on the results of tests conducted, 60% of users declare features in applications that are made is considered good in answering the needs of the enterprise, while the remaining 40% is considered adequate. Overall this application is good enough.